Roadbed disease repair method considering grouting pressure, grouting material, soil texture type and disease type
By considering the grouting pressure, grouting material, soil type and disease type, the problem of insufficient compatibility between grouting materials and grouting objects in the prior art is solved, and a more efficient and economical roadbed disease repair effect is achieved.
Patent Information
- Application Number
- CN202510035858.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-03-21
AI Technical Summary
In the roadbed grouting repair, the prior art simply pursues the best performance of the grouting material itself, and ignores the compatibility of grouting materials, grouting objects and grouting processes, resulting in a general disease repair effect and an increase in cost.
Provide a roadbed disease repair method that considers grouting pressure, grouting material, soil type and disease type. By judging the roadbed soil type and disease type, selecting appropriate grouting materials and grouting pressure, and optimizing grouting process to improve the repair effect and reduce costs.
By comprehensively considering multiple factors, the roadbed disease repair effect is improved, the number of grouting times and construction costs are reduced, and the economic effect is significantly improved.
Smart Images

Figure CN119663838A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of road maintenance, and relates to a roadbed disease repair method that takes into account grouting pressure, grouting materials, soil type and disease type. Background Art
[0002] The total mileage of highways has increased rapidly, road diseases have emerged in an endless stream, their forms are complex and changeable, and they are difficult to control, becoming a major problem in highway maintenance.
[0003] Trenchless grouting of roads is the main technical method for maintenance. Road grouting uses portable deflectometers or ground penetrating radars to detect quality defects in road structures and form grouting plans. Then, through drilling, the grouting pipe is used to evenly inject the slurry into the road structure defects in layers under a certain pressure. However, the current selection of grouting pressure is often based on experience, and the selection of grouting materials is based on the principle of optimal strength. At present, the research on road subgrade grouting mainly focuses on the preparation method and performance characterization of grouting materials, including the composition of precursor materials, alkali activator modulus, dosage, water-solid ratio, etc., which affect the performance of grouting materials. However, simply pursuing the optimal performance of the grouting material itself, while ignoring the compatibility of the grouting material, grouting object and grouting process, often leads to mediocre damage repair effects. Summary of the invention
[0004] In order to solve the above problems, the present invention provides a roadbed disease repair method taking into account grouting pressure, grouting materials, soil type and disease type, thereby improving the repair effect while reducing costs, and overcoming the drawbacks of the prior art of simply pursuing the optimal performance of the grouting material itself and the maximum grouting pressure.
[0005] The technical solution adopted by the present invention is a method for repairing roadbed damage taking into account grouting pressure, grouting materials, soil type and damage type, characterized in that it comprises the following steps:
[0006] Step 1, determining whether the roadbed soil type is clay sand or low liquid limit clay;
[0007] Step 2, determine whether the damage repair type is pure hollow repair or loose repair;
[0008] Step 3, selecting grouting materials and grouting pressure according to the influence of grouting materials and grouting pressure on the repair effect of different diseases of different roadbed soils.
[0009] Furthermore, the method for determining the influence of the grouting material and grouting pressure on the repair effect of different diseases of different roadbeds is specifically as follows:
[0010] The repair tests of low liquid limit clay and clayey sand roadbed are carried out separately; the repair of low liquid limit clay and clayey sand roadbed damage is divided into grouting hole repair, pure void repair, loose repair and interface repair; the influence of grouting materials and grouting pressure on the repair effect of grouting holes is obtained through indoor grouting hole repair test, the influence of grouting materials and grouting pressure on the repair effect of voids is obtained through pure void repair test, and the influence of grouting materials and grouting pressure on the repair effect of looseness is obtained through loose repair test;
[0011] When multiple grouting materials have the same repair effects on grouting hole repair, pure void repair, and loose repair, the grouting material is further selected based on the interface repair effect. The better the interface repair effect, the more beneficial it is to the overall effect of grouting repair.
[0012] Furthermore, the grouting material is set with a variety of different mix ratios, and the various different mix ratios correspond to different properties of the grouting material, including setting time, fluidity, compressive strength and shear strength; the grouting materials G1 to G6 respectively represent that the fluidity decreases successively, the setting time gradually decreases, and the compressive strength gradually increases; the shear strength of the grouting materials G1 to G5 gradually increases, and the shear strength of G6 is between G3 and G4.
[0013] Furthermore, the influence of the grouting material and grouting pressure on the repair effect of different diseases of low liquid limit clay roadbed is as follows: the grouting materials selected for grouting holes and pure void repair are G4-G6, and the grouting pressure ranges from 0.5 to 1.5 MPa.
[0014] On the basis of pure debulking, loose repair improves the fluidity of grouting materials as the loose thickness increases; when the loose thickness of low liquid limit clay roadbed is ≤10mm, the grouting pressure is 1~1.5MPa; when the loose thickness is greater than 10mm, the grouting pressure is 2.0~5MPa.
[0015] Furthermore, the influence of the grouting material and grouting pressure on the repair effect of different diseases of clay sand roadbed is as follows: the grouting pressure is 0.5-1.5MPa; if the compaction degree is 90% or 96%, the grouting material selected for the roadbed grouting hole repair is G4-G6; if the compaction degree is 93%, the grouting material selected for the roadbed grouting hole repair is G1-G6;
[0016] The grouting material selected for pure void repair is G4~G6, and the grouting pressure is 0.5~1.5MPa;
[0017] For loose repair, the amount of alkali activator in the grouting material is increased as the loose thickness increases; when the loose thickness of clay sand roadbed is ≤10mm, the grouting pressure is 1~1.5MPa; when the loose thickness is greater than 10mm, the grouting pressure is 1.5~5MPa.
[0018] Further, the steps of the indoor grouting hole repair test are:
[0019] Preparation of subgrade soil samples: Mix and stew the subgrade soil according to the optimal moisture content to ensure uniform distribution of moisture in the subgrade soil; the test compaction degree is set at 90%, 93% and 96%;
[0020] The mixture is poured into a mold to prepare a cylindrical specimen, the cylindrical specimen is placed in a standard curing room for curing, and a grouting hole is drilled at the center of the specimen;
[0021] Place the prepared sample into the grouting mold, inject different grouting materials into the reserved grouting holes according to the preset grouting pressure, and stop grouting until the grouting holes are completely filled; demould, place in a standard curing room for curing to the specified age, and then test the compressive strength;
[0022] The compressive strength variation law of grouting holes repaired with different grouting materials under the same compaction condition, the compressive strength variation law of grouting holes repaired with different compaction degrees under the same grouting material condition, and the compressive strength variation law of grouting holes repaired with different grouting pressures under the same compaction degree and the same grouting material condition were obtained.
[0023] Further, the steps of the loose repair test are:
[0024] Prepare roadbed specimens with different loose thicknesses, and the loose thickness of pure voids is zero;
[0025] Inject the grouting material into the mold. Each time grouting is performed, the grouting gun head is extended to the middle position of the grouting container. Different grouting materials are injected according to the preset grouting pressure to ensure that the mold gap is completely filled, and then stop grouting; demoulding, placing in a standard curing room for curing to the specified age, and then testing the compressive strength;
[0026] The compressive strength variation law of repairs with different grouting materials under the same loose thickness, the compressive strength variation law of repairs with different loose thicknesses under the same grouting material conditions, and the compressive strength variation law of repairs with different grouting pressures under the same loose thickness and the same grouting material conditions were obtained.
[0027] Furthermore, the grouting material uses CFBFA and GGBS as precursor materials.
[0028] The beneficial effects of the present invention are:
[0029] (1) Traditional roadbed repair relies solely on empirical methods to select grouting pressure and grouting materials, which increases costs and results in average grouting repair effects. The present invention considers the compatibility of grouting pressure, grouting materials, soil type, and disease type, taking into account both cost and roadbed repair effects.
[0030] (2) The present invention can select grouting pressure and grouting materials according to the roadbed soil type and disease type, select the mix ratio according to the performance of the grouting material, and select the grouting equipment according to the grouting pressure, so as to form targeted grouting materials and grouting processes, and complete the accurate and efficient repair of roadbed diseases. This avoids the traditional construction that relies solely on experience, resulting in mediocre repair effects of roadbed diseases and increased risks of secondary road maintenance.
[0031] (3) The present invention comprehensively considers multiple factors in grouting, improves the effect of roadbed disease repair, and effectively solves the problem that the grouting target cannot be achieved in one grouting, and a second grouting or even a third grouting is performed. The number of grouting times is reduced, the construction cost is saved, and the economic effect is significant. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0033] Figure 1 Schematic diagram of roadbed grouting in an embodiment of the present invention.
[0034] Figure 2 This is the XRD analysis of the precursor material CFBFA in the embodiment of the present invention.
[0035] Figure 3 is the particle size distribution of the precursor materials CFBFA and GGBS in the embodiments of the present invention.
[0036] Figure 4 These are the morphological characteristic diagrams of the precursor materials in the embodiments of the present invention; Figure a is CFBFA, and Figure b is GGBS.
[0037] Figure 5 These are two types of roadbed soil particle sizes in the embodiments of the present invention.
[0038] Figure 6 1 is the XRD diagram of two roadbed soils in the embodiment of the present invention.
[0039] Figure 7 It is the fluidity and water bleeding rate of the grouting materials with different CFBFA contents in the embodiments of the present invention.
[0040] Figure 8 is the setting time of the grouting materials with different CFBFA contents in the embodiment of the present invention.
[0041] Fig. 9 is the compressive strength of the specimens with different CFBFA contents in the embodiments of the present invention.
[0042] Fig.10 is the flexural strength of the specimens with different CFBFA contents in the embodiments of the present invention.
[0043] Fig.11 This is a comparison of the repair effects of CLS grouting holes under different compaction degrees in the embodiments of the present invention; Figure a is cured for 7 days, and Figure b is cured for 28 days.
[0044] Fig.12 1 is a comparison of the effects of SC grouting hole repair under different compaction degrees in the embodiments of the present invention; Figure a is cured for 7 days, and Figure b is cured for 28 days.
[0045] Fig.13 It is pure hollow repair (0cm) in the embodiment of the present invention.
[0046] Fig.14 This is a test of the repair effect of CLS roadbed voids with different loose thicknesses in an embodiment of the present invention.
[0047] Fig.15 This is a test of the repair effect of SC roadbed with different loose thicknesses in the embodiment of the present invention.
[0048] Fig.16 This is the loosening repair effect of CLS in the embodiment of the present invention; Figure a is loose by 10mm, Figure b is loose by 20mm, and Figure c is loose by 30mm.
[0049] Fig.17 This is the SC loosening repair effect in the embodiment of the present invention; Figure a is loose by 10 mm, Figure b is loose by 20 mm, and Figure c is loose by 30 mm.
[0050] Fig.18 Graph (a) shows the effect of compaction on the shear strength of the grouting material-CLS interface in the embodiment of the present invention; graph (b) shows the compaction at 90%, graph (c) shows the compaction at 96%, and graph (d) shows the cohesion.
[0051] Fig.19 It is the cross section of the failure specimen in the CLS soil direct shear strength test in the embodiment of the present invention.
[0052] Fig. 20 3 is the effect of compaction degree on the shear strength of the grouting material-SC interface in the embodiment of the present invention; wherein (a) shows a compaction degree of 90%, (b) shows a compaction degree of 93%, (c) shows a compaction degree of 96%, and (d) shows cohesion.
[0053] Fig.21 It is the cross section of the failure specimen in the direct shear strength test of SC soil in the embodiment of the present invention.
[0054] Fig. 22It is the XRD of the soil at the slurry-soil interface of the direct shear sample with a compaction degree of 96% in the embodiment of the present invention; wherein (a) is CLS and (b) is SC.
[0055] Fig.23 These are the SEM results of the slurry-soil interface in the embodiments of the present invention; Figure a: CLS-G5 is magnified 1000 times, Figure b: CLS-G5 is magnified 5000 times, Figure c: SC-G5 is magnified 1000 times, and Figure d: SC-G5 is magnified 5000 times.
[0056] Fig.24 It is the result of EDS line scan CLS-G5 in the embodiment of the present invention.
[0057] Fig.25 It is the result of EDS line scan SC-G5 in the embodiment of the present invention.
[0058] Fig.26 It is a flow chart of an embodiment of the present invention.
[0059] Fig. 27 It is a structural schematic diagram of a grouting mold in an embodiment of the present invention.
[0060] In the figure, 1. bolt, 2. flange plate, 3. grouting hole, 4. exhaust hole. DETAILED DESCRIPTION
[0061] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0062] The basic concept of the embodiment of the present invention is as follows:
[0063] Due to the high cost and the inability of the same roadbed soil to form the required disease types in a short period of time, it is difficult to obtain the influence of grouting materials and grouting pressure on the repair effects of different diseases of different roadbed soils based on the actual roadbed disease repair effects. At present, the most common method is to conduct indoor model tests to simulate roadbed diseases, perform grouting repairs, and then study the repair effects. If the roadbed disease type is imitated indoors (that is, imitate a whole, full-scale roadbed disease test), the cost will be greatly increased, and only the overall repair effect can be verified. It is difficult to obtain the influence of grouting materials and grouting pressure on the repair effects of different diseases of different roadbed soils. In addition, the slurry-soil interface repair effect cannot be obtained through road disease repair effect tests. Ignoring this key indicator will make it difficult to achieve the best roadbed disease repair effect. The embodiment of the present invention divides the roadbed disease repair into grouting hole repair, pure void repair, loose repair and interface repair; the influence of grouting materials and grouting pressure on the grouting hole repair effect is obtained through indoor grouting hole repair test, the influence of grouting materials and grouting pressure on the void repair effect is obtained through pure void repair test, and the influence of grouting materials and grouting pressure on the loose repair effect is obtained through loose repair test; the interface repair effect can further verify the overall repair effect. When the repair effects of several grouting materials on grouting hole repair, void repair and loose repair are equivalent, the grouting material can be further selected according to the interface repair effect. The interface repair effect affects the interaction between the slurry-soil interface, and then affects the later durability. The better the interface repair effect is, the more beneficial it is to the overall effect of grouting repair.
[0064] Embodiment A roadbed disease repair method considering grouting pressure, grouting materials, soil type and disease type, such as Fig.26 As shown, the following steps are included:
[0065] Step 1, determine the roadbed soil type, clay sand and low liquid limit clay;
[0066] Step 2, determine the type of disease, pure hollowing and looseness, where looseness is accompanied by hollowing;
[0067] Step 3, selecting grouting materials and grouting pressure according to the influence of grouting materials and grouting pressure on the repair effect of different diseases of different roadbed soils.
[0068] Different grouting material mix ratios affect the performance of grouting materials, and the performance of grouting materials affects the grouting process. The performance of grouting materials, grouting process and grouting objects jointly affect the grouting repair effect. The variation law of grouting material performance (including setting time, fluidity, compressive strength, shear strength) under different mix ratios was studied, and then the repair effects of voids, looseness, grouting holes, interface strength, etc. under different conditions were studied, and different grouting pressures were considered at the same time. Through microscopic tests, scanning electron microscopy, energy spectrum analysis and XRD, the interaction between grouting materials and roadbed soil was analyzed, and the mechanism of grouting materials repairing roadbed diseases was further revealed, and the evolution law of grouting repair effect was verified.
[0069] The method for determining the influence of grouting materials and grouting pressure on the repair effects of different diseases of different roadbed soils includes the following steps:
[0070] S1, the roadbed disease repair is divided into grouting hole repair, pure void repair, loose repair and interface repair. The grouting repair effect of these four parts will affect the overall grouting repair effect of the roadbed, such as Figure 1 shown.
[0071] S2, grouting hole repair, according to the "Highway Roadbed Design Code" (JTG D30-2015), the compaction degree of highway roadbed filling material shall not be less than 90%, so the test compaction degree is set at 90%, 93% and 96%. Preparation of roadbed soil samples, the roadbed soil is mixed and stewed according to the optimal moisture content for 24 hours to ensure uniform moisture distribution in the roadbed soil. Then the mixture is poured into the mold for sample preparation and testing. The diameter of the cylindrical specimen is 50mm and the height is 100mm. The specimen is placed in a standard curing room for curing for 7 days, and then the specimen is returned to the three-petal mold and a hole is drilled in the center of the specimen with a diameter of 16mm. The prepared specimen is placed in the grouting mold, and the grouting material is injected into the reserved grouting hole position according to the preset grouting pressure for 5 minutes to ensure that the grouting hole is completely filled, and then the grouting is stopped. After 24 hours, the mold is removed and placed in a standard curing room for curing to the specified age, and then tested.
[0072] The structure of the grouting mold is as follows Fig. 27 As shown, it includes bolts 1, flange plates 2, grouting holes 3 and exhaust holes 4. The inner wall of the grouting container has a diameter of 50 mm and a height of 100 mm.
[0073] S3, loose and hollow repair, in actual engineering, the hollow of roadbed is often formed by the further development of loose roadbed soil. In fact, loose roadbed is often accompanied by hollowing. In order to verify the influence of loose thickness of roadbed soil and grouting pressure on the repair effect of loose roadbed, a test on the repair effect of loose and hollow roadbed with different loose thickness was designed. First, the two kinds of soil were filled into a grouting container with a diameter of 50mm and a height of 100mm in a natural stacking manner, and then the mass of the two kinds of soil were weighed respectively, and samples were prepared according to 0%, 10%, 20% and 30% of their respective masses. The corresponding samples were recorded as loose thickness 0mm, 10mm, 20mm and 30mm respectively. Finally, the grouting material was injected into the mold. Each time the grouting was performed, the grouting gun head was extended to the middle position of the grouting container. The grouting pressure was 0.5MPa, 1MPa and 1.5MPa. The grouting lasted for 5 minutes to ensure that the mold gap was completely filled, and then the grouting was stopped. After 24h, the mold was demoulded and placed in a standard curing room for 7d for testing.
[0074] S4, shear strength of slurry-soil interface. First, use a ring cutter mold (diameter 61.8mm, height 20mm) to prepare cylindrical soil samples with a diameter of 61.8mm and a height of 10mm according to compaction degrees of 90%, 93% and 96%, and then pour the grouting material to fill the remaining gaps in the ring cutter mold (the reason why the grouting machine is not used for grouting in this process is that the grouting material will destroy the sample under the action of the grouting pressure, so the interface shear strength tested cannot reflect the interface bonding situation, and it is likely to be accompanied by the strength of the shear hardening grouting material, affecting the bonding effect of the slurry-soil interface), put it in a standard curing room for 7 days, and then test its shear strength.
[0075] S5, take 1cm 3 The slurry-soil interface sample (i.e. the sample after S4 curing) was subjected to scanning electron microscopy and energy spectrum test, and 2 grams of slurry-soil interface sample was taken for XRD test. The strength formation mechanism was further analyzed. The interface strength was tested first. After the strength test, a complete sample (half soil and half slurry) became two samples, one side was pure soil and the other side was grouting material. S5 took the grouting material side, and the test area was the slurry-soil interface.
[0076] S6, grouting material raw material selection, CFBFA and GGBS are used as precursor materials. The chemical composition of the precursor material is tested by X-ray fluorescence spectrometry, and the results are shown in Table 1, indicating that the main components are SiO2, Al2O3 and CaO, among which CFBFA contains some unstable components SO3 and f-CaO (free calcium oxide). The XRD analysis of CFBFA is shown in Figure 2 As shown, CFBFA contains a large amount of quartz, lime, calcite and albite, while GGBS has no obvious characteristic peaks, indicating that it exists in an amorphous glass phase. The particle size analysis of the two materials was carried out using a Mastersizer 3000 laser particle size analyzer. The results are shown in Figure 3 As shown in the figure. GGBS and CFBFA have finer particles, which are specifically manifested in smaller values of D10, D50 and D90. The microstructure of the precursor material was analyzed using a scanning electron microscope, as shown in the figure. Figure 4 As shown, the microstructure of CFBFA particles is loose and porous, while the surface of GGBS is relatively smooth and has some spherical particles. The micromorphology of the precursor material will affect the performance of the grouting material. The alkaline activator was prepared using flake sodium hydroxide (purity> 99%) and water glass solution (SiO2 is 27.3wt.%, Na2O is 8.54wt.%, H2O is 64.16wt.%) as raw materials.
[0077] Table 1 Main chemical components of CFBFA and blast furnace slag (data unit wt.%)
[0078] Solid Waste T-CaO f-CaO <![CDATA[SiO 2 ]]> <![CDATA[Al 2 THE 3 ]]> <![CDATA[Fe 2 THE 3 ]]> MgO <![CDATA[K 2 The]]> <![CDATA[SO 3 ]]> <![CDATA[TiO 2 ]]> CFBFA 17.02 1.68 55.17 10.87 7.22 1.60 1.21 3.30 0.48 Blast furnace slag 41.44 — 30.24 15.47 0.32 8.05 0.44 2.63 0.88
[0079] S7, subgrade soil performance test, the basic performance test results of the two subgrade soils are shown in Table 2, CLS is low liquid limit clay, SC is clayey sand. The particle size distribution of the two soils is shown in Table 2. Figure 5 The XRD test results of the two soils are shown in Figure 6 As shown in Figure 2, particle size and composition are important factors affecting slurry-soil reaction.
[0080] Table 2 Basic physical properties of two types of roadbed soil
[0081]
[0082] S8, grouting material performance test, grouting material mix ratio is shown in Table 3; fluidity and water seepage test results are shown in Figure 7 First, the fluidity of the roadbed grouting material is required to be no more than 17s, otherwise it will affect the grouting repair effect. In principle, the smaller the water seepage rate, the better, preferably no more than 2%. The setting time test results are as follows: Figure 8 The setting time requires that the initial setting time is not less than 40 minutes and the final setting time is not more than 400 minutes. The compressive strength test results are as follows Fig. 9 , the 28-day strength requirement for roadbed grouting is no less than 2.47MPa, Fig. 9 All the formulas meet the requirements, and the flexural strength (i.e. shear strength) results are as follows Fig.10 The specification does not make any requirements, but the greater the flexural strength, the better. Figure 7-Figure 10 In the figure, the horizontal axis corresponds to the sample names from right to left, namely G1 to G6.
[0083] Table 3 Geopolymer grouting material design (data unit: g)
[0084] Sample name CFBFA GGBS Sodium silicate Sodium hydroxide water G1 65 35 27.93 7.07 47.08 G2 60 40 27.93 7.07 47.08 G3 55 45 27.93 7.07 47.08 G4 50 50 27.93 7.07 47.08 G5 45 55 27.93 7.07 47.08 G6 40 60 27.93 7.07 47.08
[0085] S9, grouting hole repair effect. The repair of grouting holes is the basis of road grouting repair work, and its repair quality directly affects the effect of the entire road grouting repair. Fig.11 The effect of CLS (low liquid limit clay) grouting hole repair under different compaction degrees is shown. Fig.11 It can be observed that the strength of the repaired specimens from G1 to G6 grouting holes gradually increases. This is mainly because the grouting holes in the center of the specimens are filled with grouting materials with higher strength. The strength development law of the repaired specimens is consistent with the strength development law of the grouting materials, which shows that grouting materials with higher strength have better repair effects. In addition, Fig.11 It also shows that under the same grouting material conditions, as the compaction degree increases, the strength of the sample after grouting repair also increases accordingly. This is because after the grouting material is injected into the grouting hole, it reacts with the soil particles on the outer wall of the grouting hole. After the grouting liquid is injected, the alkali activator and part of the precursor particles penetrate into the soil, fill the internal pores, and the silicon, aluminum and calcium components in the soil participate in the reaction to form a small amount of geopolymer gel. At the same time, the alkali activator in the geopolymer grouting material penetrates into the soil, resulting in a decrease in the content of the alkali activator in the grouting material, affecting the strength of the grouting material. The greater the compaction degree, the less the alkali activator penetrates, and the smaller the negative impact on the grouting material. In addition, the grouting material forms an internal structure in the grouting hole, and the outside is tightly wrapped by the roadbed soil. The greater the compaction degree of these wrapped soils, the greater the compressive resistance provided. At the same time, the outer soil provides confining pressure to the inner ring grouting material, making the overall strength of the sample greater.
[0086] contrast Fig.11 Figures a and b show that the compressive strength of the sample is further enhanced after 28 days of curing. This phenomenon can be attributed to the reaction between the alkali activator that penetrates into the soil and the weakly reactive silicon, aluminum and calcium components in the soil. This reaction cycle is relatively long, so the strength is further improved after 28 days. At the same time, according to Fig. 9 As shown in the figure, the grouting material filling the grouting hole also increases with the increase of curing time. These factors work together to further improve the 28-day compressive strength of the grouting hole repair sample. Fig.11 Based on the data of a-11b, it can be concluded that G4 to G6 grouting materials should be given priority in the repair of grouting holes in CLS (low liquid limit clay) roadbed to achieve efficient repair of grouting holes.
[0087] Fig.12The comparison of the effects of SC (clay sand) grouting hole repair under different compaction degrees is shown, and the results show that the grouting hole repair effect of SC samples is more significant. This phenomenon occurs because the unconfined compressive strength of SC samples without grouting is much smaller than that of CLS samples, which makes the grouting hole repair effect of SC samples with the same grouting material more prominent. From G1 to G6, the strength change law of SC samples is consistent with that of CLS samples, which is mainly affected by the grouting material. The strength of the repaired samples is mainly provided by the grouting material, so the change law of the overall strength is not affected by the soil type. However, unlike the CLS samples, the strength of the SC grouting hole repaired samples does not increase with the increase of soil compaction, but reaches the best repair effect when the compaction degree is 93%. For G1 to G3 grouting materials, the strength of SC samples with 90% compaction degree is lower than that of samples with 96% compaction degree; while for G4 to G6 grouting materials, the strength of SC samples with 96% compaction degree is lower than that of samples with 93% compaction degree. The reason for this difference may be that at 90% and 96% compaction, SC, as sand, has low cohesion and low compressive strength. Therefore, the confining pressure provided by sand has limited effect on the improvement of grouting material strength. Another reason is that there are differences in the gaps between soil particles in SC samples at different compaction. The greater the compaction, the smaller the gaps between soil particles, resulting in a decrease in the amount of grouting material infiltrating into the pores, resulting in a phenomenon that the greater the compaction, the worse the repair effect. For G1 to G3 grouting materials, the sample strength at 90% compaction is lower than that at 96% compaction. The reason is that at 90% compaction, the gaps between soil particles are too large, resulting in the majority of alkali activators in the grouting material infiltrating into the gaps, while only a small amount of precursor material enters the gaps due to the influence of particles. The ability of soil particles themselves to participate in alkali excitation reactions is poor. These factors limit the reaction of the grouting material entering the gaps, and can only repair the gaps between some soil particles, resulting in weaker overall strength. At 96% compaction, the gaps between the soil particles in the sample are smaller than those at 90%. Even if the amount of grouting material immersed is small, the effective repair ratio of the immersed grouting material is higher due to the small gaps between the soil particles, so the repair effect is better. As for the better repair effect of grouting materials at 93% compaction, the reason is that the gaps between the soil particles in the SC sample at 93% compaction are moderate, the ratio of alkali activator and precursor material in the immersed grouting material is appropriate, and more geopolymer gel is formed by reaction to fill the gaps between the soil particles, so the repair effect is better. Based on the above analysis, when the roadbed soil is SC (clay sand), if the compaction is 90%, G4 to G6 grouting materials should be selected; if the compaction is 93%, G1 to G6 grouting materials can be selected; if the compaction is 96%, G4 to G6 grouting materials should be selected to achieve the best grouting hole repair effect.
[0088] S10, air gap repair;
[0089] The voiding of roadbed will seriously damage the durability of the road, especially large-scale voiding may cause road collapse, posing a serious threat to driving safety. Therefore, the repair effect of voiding of roadbed is directly related to the success or failure of the overall repair of roadbed grouting. In order to eliminate the interference of sample type on sample strength, the grouting sample with pure voiding (i.e., the thickness of loose layer is 0mm) was first analyzed. Fig.13 As shown, Fig. 9 Compared with the samples, the strength of the samples decreased, which was mainly due to the increase in the surface area of the samples. The strength change law of the grouting materials from G1 to G6 is similar to Fig. 9 This rule is mainly determined by the ratio of grouting materials. Fig.13 , it can be found that the strength of the sample is mainly affected by the ratio of the grouting material, while the effect of the grouting pressure on the strength of the sample is relatively small. This is because under different grouting pressures, the grouting material cannot be compressed to a denser state, and the internal structure of the sample is mainly determined by the ratio of the grouting material. In short, the ratio of the grouting material is the key factor affecting the strength of the sample, while the effect of the grouting pressure is relatively limited. These findings have important guiding significance for optimizing the ratio of grouting materials and grouting technology, and improving the effect of roadbed degassing repair.
[0090] pass Fig.13 The study found that the grouting pressure has little effect on the void repair effect. Therefore, when considering the effect of loose soil thickness on the void repair effect, the grouting pressure is not considered, and the grouting material is poured into the grouting mold. Fig.14 The following are the results of the CLS (low liquid limit clay) void repair test under different loose thicknesses. Fig.14 It can be seen that no matter what kind of loose thickness, the strength of the sample is greatly affected by the grouting material, and the loose thickness has little effect on the void repair effect. This is because the grouting material in the experiment has good fluidity and can easily fill the void area, while the strength of the grouting material itself varies greatly, so it is greatly affected by the grouting material itself. Fig.14 and Fig.13 It can be seen that when the loose thickness is 10mm, the strength of the void area of the sample under the same grouting material is significantly reduced. The reason for this is that the loose roadbed soil will infiltrate the alkali activator and a small amount of precursor material, causing the alkali activator and precursor ratio of the grouting material in contact with the loose soil area to change, resulting in insufficient local strength in the repaired void area, which in turn affects the overall strength of the void repair. Fig.14 It can also be found that with the increase of loose thickness, the strength after void repair is lower; the larger the loose thickness, the greater the amount of alkali activator immersed, the lower the content of alkali activator in the grouting material filling the void area, which in turn leads to a decrease in the strength of the sample.
[0091] Fig.15The test results of the repair effect of SC (clay sand) roadbed with different loose thicknesses. The strength change law of the specimens and the strength change law with loose thickness are consistent with the CLS roadbed repair. Under the same conditions, the repair strength of SC roadbed soil is slightly lower than that of CLS roadbed soil. The main reason for this phenomenon is that SC belongs to sandy soil and has loose bonding between particles and large porosity compared with CLS clay, which leads to more alkali activators being immersed in the roadbed soil. The reduction of alkali activators leads to changes in the original mix ratio, resulting in reduced strength.
[0092] Loose repair;
[0093] Loose repair is mainly reflected in the cause of roadbed hollowing. The cause of roadbed hollowing is leakage of internal pipes of the roadbed. Minor leakage is often difficult to detect. Liquid leakage erodes and washes the roadbed soil, causing the roadbed to be hollowed out and accompanied by a small amount of loose particles. For this reason, two roadbed repair effects with different loose thickness of soil were designed. The CLS loose repair effect is as follows Fig.16 , grouting pressure and loose soil thickness have significant effects on the repair effect. As the grouting pressure decreases, the effect of grouting materials is small. This is because the amount of grouting material that penetrates into the loose soil is very limited, and it is difficult to significantly improve the strength of the loose soil. Since the distance that the grouting material penetrates into the loose soil is very limited, and the amount of penetration is very small, the type of grouting material has little effect on the loose repair. Under high grouting pressure, the grouting liquid flushes the loose soil and the slurry fills part of the loose soil area. Therefore, under high grouting pressure, the loose repair effect is significant. As the loose thickness increases, the loose soil repair effect is significantly reduced. This is because the grouting liquid cannot break through the loose soil layer under the action of the grouting pressure. The soil layer that is not filled with the grouting liquid can only rely on a small amount of grouting material to penetrate into the soil layer to increase the strength. However, the penetration effect is very limited, resulting in a significant decrease in the loose repair effect. From Fig.16 It can also be seen that no matter what kind of loose thickness, the high grouting pressure is always more effective. This is because the penetration effect of the grouting material is better under high grouting pressure, but the grouting material is limited in depth under grouting pressure. During the compressive strength test, the specimen will be damaged from the weak area. Under high pressure, the loose soil is penetrated by more grouting materials, so the improvement effect is better. On the one hand, the infiltrated grouting material cements the soil particles to form strength. On the other hand, the alkali activator in the grouting material can have a weak geological polymerization reaction with the silicon, aluminum and calcium components inside the soil particles, further enhancing the strength of the loose soil. In addition, a cation exchange reaction may occur between the grouting material and the soil particles, that is, the K inside the soil particles + 、Na + NH 3+ , and Al inside the grouting material 3 + , Fe 3+ Mg 2+Cation exchange occurs, which can reduce the thickness of the soil electron layer, further increase the density of the soil, and thus increase the strength.
[0094] Fig.17 Under the same conditions, the grouting repair effect is affected by the soil type. Loose clay sand soil is more easily repaired by low grouting pressure. When the loose thickness of clay sand does not exceed 10mm, the grouting pressure is preferably 1MPa. When the loose thickness exceeds 10mm, the grouting pressure is preferably 1.5MPa, which provides a basis for the selection of grouting parameters and grouting materials.
[0095] S11, slurry-soil interface strength;
[0096] Studying the shear strength of the slurry-soil interface is helpful to analyze the interaction between slurry and soil. Studying the shear strength of the slurry-soil interface under different soil types and different compaction degrees can select appropriate grouting materials according to soil type and compaction degree, and further improve the grouting repair effect. Fig.18 As shown in the figure. The maximum shear stress of samples G1 to G6 increased significantly. The formation of geopolymer gel at the slurry-soil interface increased the difficulty of shear failure of the samples, resulting in a continuous increase in the maximum shear stress. The geopolymer gel filled the pores of CLS soil particles and cemented the soil particles to form larger soil particle aggregates. The formation of these aggregates helped to improve the shear strength of the slurry-soil interface. Fig.18 In Figures (a) to (c), the compaction degree of CLS gradually increases, and the shear strength of the pure CLS sample increases significantly, but the shear strength of the slurry-soil interface gradually decreases. This is because the increase in compaction reduces the voids between soil particles, and the increase in the density of the soil body leads to an increase in the shear resistance of the sample, while the reduction in voids reduces the interaction between the grouting material and the soil particles, resulting in a less obvious increase in the shear strength of the slurry-soil interface with a greater compaction degree. It can also be seen from the figure that the interface shear strength of the grouting material gradually increases from G1 to G6 samples. This is because the strength of the G1 to G6 grouting material gradually increases, generating more geopolymer gel, which has a stronger bonding ability under the same compaction degree, thus increasing the shear strength of the slurry-soil interface.
[0097] like Fig.18 As shown in Figure (d), the cohesion of the slurry-soil interface gradually increases as the grouting material changes from G1 to G6. The grouting material penetrates into the gaps between the CLS particles to produce a cementing effect, which hinders the movement of the CLS particles and increases the shear strength of the slurry-soil interface. Compared with the pure CLS sample, the maximum increase in cohesion at 90%, 93% and 96% compaction degrees is 85.7%, 50.5% and 29.0%, respectively. By analyzing Fig.18 It was found that the internal friction angle of the shear strength parameter of the slurry-soil interface did not change much regardless of the compaction degree, and was only greatly affected by the compaction degree of the roadbed soil.
[0098] Fig.19 The cross-sectional view of the sample after the shear strength test. For all samples, a certain amount of CLS soil particles were observed on the surface of the grouting material, and the number of soil particles gradually increased from G1 to G6, which indicates that the grouting materials from G1 to G6 have stronger bonding ability and can improve the interface shear strength to a greater extent. As the compaction degree increases from 90% to 96%, the CLS particles on the surface of the grouting material gradually decrease, which is due to the reduction of the gaps between the particles on the surface of the CLS sample. It also proves that the higher the compaction degree, the smaller the improvement in the interface shear strength.
[0099] The shear strength results of SC paste-soil interface are as follows: Fig. 20 As shown in the figure, the shear strength of the grouting materials increases gradually from G1 to G6, which is the same as the CLS results. The difference is that the increase is smaller, which can be attributed to the performance characteristics of SC and CLS. The SC particles are loose and have low cohesion, which makes it difficult to bond the particles. Even if the grouting material penetrates into the gaps between SC particles and plays a certain bonding role, these bonding effects do not significantly improve the shear strength of SC particles that are more difficult to bond. Fig. 20 It can be seen that compared with the CLS sample, the SC sample has lower shear strength and smaller cohesion. This phenomenon can be attributed to the fact that CLS is easier to bond as clay, while SC is loose and difficult to bond as sand particles. Fig. 20 It can also be seen that the shear strength of the sample is more affected by the compaction degree and relatively less affected by the grouting material. The bonding properties of the grouting materials from G1 to G6 gradually increase, resulting in a gradual increase in the shear strength of the sample. The previous test has proved that the self-strength of the grouting materials from G1 to G6 gradually increases, so the amount of grouting materials filling the gaps between soil particles at the same compaction degree is equivalent, so the interface shear strength of the G1 to G6 samples gradually increases at the same compaction degree.
[0100] Fig. 20 Figure (d) in the figure analyzes the variation of cohesion at the slurry-soil interface under different conditions. The interface cohesion gradually increases from G1 to G6 samples. This is because the grouting material penetrates into the gaps between the SC particles to produce a cementing effect, forming SC particle agglomerates, which hinder the movement of SC particles and increase the cohesion at the slurry-soil interface. Compared with the pure SC samples, the maximum increase in cohesion at 90%, 93% and 96% compaction degrees is 100.6%, 75.3% and 32.5%, respectively. Comparative analysis Fig. 20 As can be seen from Figures (a), (b) and (c) in Figure 3, the internal friction angle is more affected by the degree of compaction, while the grouting material has little effect on the cohesion.
[0101] Fig.21The direct shear strength test of SC soil destroys the cross section of the sample. Through the above test, it can be found that when the roadbed soil is clay, G4~G6 grouting materials are preferred for grouting holes and void repair. The grouting pressure has little effect. The grouting pressure ranges from 0.5 to 1.5 MPa, preferably 0.5 MPa, which can reduce the grouting cost. The thicker the loose thickness of the loose repair, the higher the grouting pressure and the fluidity of the grouting material should be to improve the grouting repair effect. When the loose thickness of the base is ≤10mm, the grouting pressure is 1~1.5MPa (1.5MPa in the embodiment); when the loose thickness is greater than 10mm, the grouting pressure is 2.0~5MPa.
[0102] When the roadbed soil is sandy, the grouting pressure has little effect on the repair effect of the grouting hole. The grouting pressure for grouting hole repair can be 0.5-1.5MPa. Considering the cost, 0.5MPa is preferred. If the pressure is less than 0.5MPa, the grouting material may not reach the designated grouting position. Excessive grouting pressure may damage the original intact roadbed. If the compaction degree of grouting hole repair is 90%, G4 to G6 grouting materials should be selected; if the compaction degree is 93%, G1 to G6 grouting materials can be used; if the compaction degree is 96%, G4 to G6 grouting materials should be selected to achieve the best grouting hole repair effect. G4 to G6 grouting materials are preferred for pure void repair, and the grouting pressure can be 0.5-1.5MPa; loose repair increases with the increase of loose thickness. The amount of alkali activator in the grouting material.
[0103] XRD analysis:
[0104] In order to explore whether the grouting material will react chemically with the roadbed soil, the soil at the grout-soil interface of the direct shear sample with a compaction degree of 96% was tested for XRD analysis and compared with the XRD of the plain soil sample to explore the grout-soil reaction. The CLS test results on the interface of CLS and grouting material G5 (CLS-G5) are shown in the figure. Fig. 22 In Figure (a), the phases in CLS-G5 include quartz, muscovite, epidote and albite, which also exist in CLS, indicating that no new phases are produced after CLS contacts with grouting materials. In fact, there is a small amount of geopolymer gel in CLS-G5, that is, a small amount of activated SiO2, Al2O3 and CaO in CLS undergoes a weak geopolymerization reaction with the precursor material in the grouting material under the action of an alkali activator. Since the geopolymer gel exists in an amorphous to semi-crystalline state, no obvious characteristic peaks appear in the CLS-G5 XRD spectrum. However, a weak diffuse peak appears in the CLS-G5 XRD spectrum corresponding to 2θ in the range of 20 to 40°. Previous studies have shown that this is the characteristic peak of geopolymer gel. Compared with the CLS XRD spectrum, the characteristic peak intensity decreases, and a very small number of characteristic peaks disappear. This indicates that some phases in CLS react with the grouting material, resulting in a decrease in the intensity of the characteristic peak.
[0105] Fig. 22 Figure (b) shows the SC-G5 interface and SCXRD spectrum. Compared with SC, the characteristic peak intensity at around 10° is significantly reduced, which indicates that actinolite (Ca2(Mg,Fe)5Si8O 22 (OH)) was dissolved by the alkaline activator in the grouting material and participated in the geopolymerization reaction, indicating that a large amount of calcium and silicon in actinolite participated in the reaction and generated CSH and CASH gels, which was confirmed in the EDS line scan results of subsequent analysis. At the same time, some dispersion peaks were generated in the range of 20° to 40° at 2θ, which were more significant than CLS-G5, indicating that the reaction between SC and the grouting material was more intense.
[0106] SEM analysis:
[0107] Analysis of the microscopic morphology of the slurry-soil interface helps to reveal the laws of slurry-soil interaction. Fig.23 The interface morphology characteristics of direct shear specimens CLS-G5 and SC-G5 were analyzed. Fig.23 In Figure a, it can be seen that some CLS particles are cemented into slurry-soil aggregates by the grouting material, and the grouting material forms a dense geopolymer gel plane. There are many hardened grouting material particles, cemented CLS particles and dense grouting material gel at the interface, and these granular materials are closely connected with the grouting material. Fig.23 In Figure b, we can see that there are a lot of hardened grouting materials. This is because the voids on the surface of the CLS specimen are filled with grouting materials, which form agglomerates of grouting materials after solidification. The slurry-soil mixture is tightly bonded, indicating that the grouting material can bond the CLS particles well. These grouting material bonds, slurry-soil bonds, and the dense plane formed by the grouting material are confirmed in the EDS line scan results.
[0108] Fig.23 Figures c and d are the SEM results of the SC-G5 interface. Fig.23 Figure c shows that many SC particles are cemented into aggregates by the grouting material. The compact morphology of the cemented bodies indicates that the grouting material has a good cementing effect on the SC particles. From the above XRD results, it can be seen that a weak geological polymerization reaction will occur between the grouting material and the SC particles to generate partial gel. These interactions promote the cementing effect of the grouting material on the SC particles. Fig.21 ) It can also be found that the SC particles are cemented into a large number of agglomerates by the grouting material. Compared with CLS, the grouting material has a more significant cementing effect on SC particles. Fig.23In the d figure, a large number of grout-soil aggregates can be seen, indicating that the grouting material has a strong bonding effect on the SC. Similarly, these hardened grouting materials are larger than CLS because the interaction between SC particles is weaker and the gaps between particles are larger. These gaps are filled with grouting materials to form larger grouting material aggregates. The SC particles are tightly bonded by the grouting material, which is also the reason why the shear strength of the interface between the grouting material and SC is significantly improved.
[0109] EDS line scanning can help analyze the elemental composition of different microscopic morphologies and infer the material composition represented by different morphologies. Fig.24 The EDS line scan position corresponds to Fig.23 In the figure b, the Na, Al and Ca content increases at 7.5-11.8 μm and 13-19 μm, indicating that these areas are hardened grouting materials. The Na, Al and Ca content is very low at 5-7.5 μm, 11.8-13 μm and 19-24 μm, indicating that these areas are the surface of the grouting material. Fig.19 It can be seen that the surface of the grouting material is covered by CLS mud, so these three sections are the hardened planes of the grouting material covered by CLS mud. In fact, EDS tests the relative content of elements of CLS, so the content of Na, Al and Ca elements is very low, and the content of Si is very high. At 0-5 microns, the relative content of Na, Al and Ca elements is between the grouting material and CLS, so this area is a slurry-soil mixed area. This area is tightly bonded and has no obvious gaps, which further proves that the grouting material has good bonding ability to CLS.
[0110] Fig.25 This is the EDS line scan result of the SC-G5 slurry-soil interface. Fig.23 In the middle d position, the content of Na, Al and Ca elements increases in the range of 3.7-8.6 μm and 13.2-18 μm, indicating that these areas are hardened grouting materials. The content of Na, Al and Ca elements in the range of 0-3.7 μm and 8.6-13.2 μm is very low, and these areas are grouting material planes covered by SC mud. The content of Na, Al and Ca elements in the range of 18-23.2 μm is between the grouting material and SC, so it is judged that this area is a slurry-soil mixed area. The morphology of this area is more compact and flat, which is the result of the cementation of the grouting material and the reaction between the grouting material and SC.
[0111] Grouting materials, grouting pressure, and roadbed soil type are all factors that affect the grouting repair effect, rather than a single factor. The influence between them cannot be obtained by a simple orthogonal test. The embodiment of the present invention divides the roadbed grouting into grouting hole repair, pure void repair, loose repair, and slurry-soil interface, which can clearly determine which influencing factors affect which properties of grouting repair, and the experiment is simple, low-cost, and can be repeated many times. The test conditions required by the user can be designed, and the influence of grouting pressure, grouting materials, soil type, and disease type on the roadbed disease repair effect can be obtained comprehensively and accurately. The embodiment of the present invention proposes a better roadbed grouting repair method, which selects grouting materials and grouting pressure according to the roadbed soil type and disease type to achieve better repair effects. The traditional method only relies on the empirical method to select grouting materials and grouting pressure, which is easy to increase the grouting cost; on the one hand, the preparation of the grouting material with the best performance increases the cost, and on the other hand, the selection of a larger grouting pressure increases the cost. Secondly, because the grouting repair effect does not meet the standard, repeated grouting increases the cost. The traditional method of selecting grouting materials is to select the higher the fluidity, the better, the lower the water seepage rate, the better, and the higher the strength, the better. According to this method, it is difficult for ordinary grouting materials to take into account all the optimal properties, and only a compromise can be selected. In the embodiment of the present invention, only G3 (CFBFA55%, GGBS45%) can be selected from G1 to G6. The method of the embodiment of the present invention can select the grouting material mix ratio, select the appropriate grouting material and grouting pressure according to the grouting pressure, grouting material, soil type and disease type, improve the grouting repair effect, reduce the number of grouting times, reduce the grouting material preparation cost, and significantly reduce the grouting repair cost.
[0112] Example 1: Clay, pure decompression, 96% compaction degree; the grouting material of the traditional method is G3 (CFBFA content is 55%), and the grouting pressure is 1.5MPa; the grouting material selected in the embodiment of the present invention according to the influence of the above grouting material and grouting pressure on the repair effect of different diseases of different roadbed soils is G6 (CFBFA content is 40%), and the grouting pressure is 0.5MPa.
[0113] Example 2: Clay, pure decompression, 93% compaction degree; the grouting material of the traditional method is G3 (CFBFA content is 55%), and the grouting pressure is 1.5MPa; the grouting material selected in the embodiment of the present invention according to the influence of the above grouting materials and grouting pressure on the repair effects of different diseases of different roadbed soils is G6 (CFBFA content is 40%), and the grouting pressure is 0.5MPa.
[0114] Example 3: Sand, pure hollowing, 96% compaction degree; the grouting material of the traditional method is G3 (CFBFA content is 55%), and the grouting pressure is 1.5MPa; the grouting material selected in the embodiment of the present invention according to the influence of the above-mentioned grouting materials and grouting pressure on the repair effects of different diseases of different roadbed soils is G6 (CFBFA content is 40%), and the grouting pressure is 0.5MPa.
[0115] Example 4: Sand, pure hollowing, 90% compaction degree; the grouting material of the traditional method is G3 (CFBFA content is 55%), and the grouting pressure is 1.5MPa; the grouting material selected in the embodiment of the present invention according to the influence of the above-mentioned grouting materials and grouting pressure on the repair effects of different diseases of different roadbed soils is G6 (CFBFA content is 40%), and the grouting pressure is 0.5MPa.
[0116] Example 5: Clay, loose (with voids), thickness 10 mm, 90% compaction degree; the grouting material used in the traditional method is G3 (CFBFA content is 55%), and the grouting pressure is 1.5 MPa; the grouting material selected in the embodiment of the present invention according to the influence of the above-mentioned grouting materials and grouting pressure on the repair effects of different diseases of different roadbed soils is G6 (CFBFA content is 40%), and the grouting pressure is 1.5 MPa.
[0117] Example 6: Clay, loose (with voids), thickness 20 mm, 93% compaction degree; the grouting material used in the traditional method is G3 (CFBFA content is 55%), and the grouting pressure is 1.5 MPa; the grouting material selected in the embodiment of the present invention according to the influence of the above-mentioned grouting materials and grouting pressure on the repair effects of different diseases of different roadbed soils is G6 (CFBFA content is 40%), and the grouting pressure is 1.5 MPa.
[0118] Example 7: Sand, loose (with voids), thickness 10 mm, 90% compaction degree; the grouting material used in the traditional method is G3 (CFBFA content is 55%), and the grouting pressure is 1.5 MPa; the grouting material selected in the embodiment of the present invention according to the influence of the above-mentioned grouting materials and grouting pressure on the repair effects of different diseases of different roadbed soils is G6 (CFBFA content is 40%), and the grouting pressure is 1.5 MPa.
[0119] Example 8: Sand, loose (with voids), thickness 30 mm, 93% compaction degree; the grouting material used in the traditional method is G3 (CFBFA content is 55%), and the grouting pressure is 1.5 MPa; the grouting material selected in the embodiment of the present invention according to the influence of the above-mentioned grouting materials and grouting pressure on the repair effects of different diseases of different roadbed soils is G6 (CFBFA content is 40%), and the grouting pressure is 1.5 MPa.
[0120] The experimental data of Examples 1-8 are shown in Table 4. The examples of the present invention have better repair effects and lower costs than traditional methods.
[0121] Table 4 Experimental data of Examples 1-8
[0122]
[0123] The above description is only a preferred embodiment of the present invention and is not intended to limit the protection scope of the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention are included in the protection scope of the present invention.
Claims
1. A method for repairing roadbed damage taking into account grouting pressure, grouting materials, soil type and damage type, characterized in that: The following steps are involved: Step 1, determining whether the roadbed soil type is clay sand or low liquid limit clay; Step 2, determine whether the damage repair type is pure hollow repair or loose repair; Step 3, selecting grouting materials and grouting pressure according to the influence of grouting materials and grouting pressure on the repair effect of different diseases of different roadbed soils.
2. A roadbed disease repair method according to claim 1 that takes into account grouting pressure, grouting materials, soil type and disease type, characterized in that: The method for determining the influence of the grouting material and grouting pressure on the repair effect of different diseases of different roadbeds is specifically as follows: The repair tests of low liquid limit clay and clayey sand roadbed are carried out separately; the repair of low liquid limit clay and clayey sand roadbed damage is divided into grouting hole repair, pure void repair, loose repair and interface repair; the influence of grouting materials and grouting pressure on the repair effect of grouting holes is obtained through indoor grouting hole repair test, the influence of grouting materials and grouting pressure on the repair effect of voids is obtained through pure void repair test, and the influence of grouting materials and grouting pressure on the repair effect of looseness is obtained through loose repair test; When multiple grouting materials have the same repair effects on grouting hole repair, pure void repair, and loose repair, the grouting material is further selected based on the interface repair effect. The better the interface repair effect, the more beneficial it is to the overall effect of grouting repair.
3. A roadbed disease repair method according to claim 2, which takes into account grouting pressure, grouting materials, soil type and disease type, characterized in that: The grouting material is set with a variety of different mix ratios, and the various different mix ratios correspond to different properties of the grouting material, including setting time, fluidity, compressive strength and shear strength; grouting materials G1 to G6 represent fluidity decreasing in sequence, setting time gradually decreasing, and compressive strength gradually increasing; grouting materials G1 to G5 have gradually increasing shear strength, and the shear strength of G6 is between G3 and G4.
4. A roadbed disease repair method according to claim 3, which takes into account grouting pressure, grouting materials, soil type and disease type, characterized in that: The influence of the grouting material and grouting pressure on the repair effect of different diseases of low liquid limit clay roadbed is as follows: the grouting material selected for grouting hole and pure void repair is G4-G6, and the grouting pressure ranges from 0.5 to 1.5 MPa; On the basis of pure debulking, loose repair improves the fluidity of grouting materials as the loose thickness increases; when the loose thickness of low liquid limit clay roadbed is ≤10mm, the grouting pressure is 1~1.5MPa; when the loose thickness is greater than 10mm, the grouting pressure is 2.0~5MPa.
5. A roadbed disease repair method according to claim 3, which takes into account grouting pressure, grouting materials, soil type and disease type, characterized in that: The influence of the grouting material and grouting pressure on the repair effect of different diseases of clay sand roadbed is as follows: the grouting pressure is 0.5-1.5MPa; if the compaction degree is 90% or 96%, the grouting material selected for the roadbed grouting hole repair is G4-G6; if the compaction degree is 93%, the grouting material selected for the roadbed grouting hole repair is G1-G6; The grouting material selected for pure void repair is G4~G6, and the grouting pressure is 0.5~1.5MPa; For loose repair, the amount of alkali activator in the grouting material is increased as the loose thickness increases; when the loose thickness of clay sand roadbed is ≤10mm, the grouting pressure is 1~1.5MPa; when the loose thickness is greater than 10mm, the grouting pressure is 1.5~5MPa.
6. A roadbed disease repair method according to claim 2, which takes into account grouting pressure, grouting materials, soil type and disease type, characterized in that: The steps of the indoor grouting hole repair test are as follows: Preparation of subgrade soil samples: Mix and stew the subgrade soil according to the optimal moisture content to ensure uniform distribution of moisture in the subgrade soil; the test compaction degree is set at 90%, 93% and 96%; The mixture is poured into a mold to prepare a cylindrical specimen, the cylindrical specimen is placed in a standard curing room for curing, and a grouting hole is drilled at the center of the specimen; Place the prepared sample into the grouting mold, inject different grouting materials into the reserved grouting holes according to the preset grouting pressure, and stop grouting until the grouting holes are completely filled; demould, place in a standard curing room for curing to the specified age, and then test the compressive strength; The compressive strength variation law of grouting holes repaired with different grouting materials under the same compaction condition, the compressive strength variation law of grouting holes repaired with different compaction degrees under the same grouting material condition, and the compressive strength variation law of grouting holes repaired with different grouting pressures under the same compaction degree and the same grouting material condition were obtained.
7. A roadbed disease repair method according to claim 2, which takes into account grouting pressure, grouting materials, soil type and disease type, characterized in that: The steps of the loose repair test are: Prepare roadbed specimens with different loose thicknesses, and the loose thickness of pure voids is zero; Inject the grouting material into the mold. Each time grouting is performed, the grouting gun head is extended to the middle position of the grouting container. Different grouting materials are injected according to the preset grouting pressure to ensure that the mold gap is completely filled, and then stop grouting; demoulding, placing in a standard curing room for curing to the specified age, and then testing the compressive strength; The compressive strength variation law of repairs with different grouting materials under the same loose thickness, the compressive strength variation law of repairs with different loose thicknesses under the same grouting material conditions, and the compressive strength variation law of repairs with different grouting pressures under the same loose thickness and the same grouting material conditions were obtained.
8. A roadbed disease repair method according to claim 2, which takes into account grouting pressure, grouting materials, soil type and disease type, characterized in that: The grouting material uses CFBFA and GGBS as precursor materials.
Citation Information
Cited By
Method for determining geopolymer improved soil roadbed maintenance time based on damage self-repairing rate
CN120493373A
Method for determining maintenance time of geopolymer improved soil subgrade based on damage self-repairing rate
CN120493373B